The bar code tattoo - Weyn, Suzanne (New York Scholastic, 2004)
Kayla is ostracized at school because she refused to get the required tattooed bar code and now she and her family must run to avoid the dangers threats against them
English stories
2
Keywords: Conformity -- Fiction; High schools -- Fiction; Identity -- Fiction; Science fiction